Analysing the awareness of generation Y youth on ‘3D’ industries through ‘3D’ info system / Emy Noor Diana Zulkiflee, Fadilah Puteh and Jasmine Ahmad - Zulkiflee, Emy Noor Diana; Puteh, Fadilah; Ahmad, Jasmine (Universiti Teknologi MARA, 2020)
3D’ is an acronym for dirty, dangerous and difficult. Also perceived as labour intensive, excessive physical work, hazardous work environment, low wages and little security, ‘3D’ industries today have a significant contribution to the Malaysian economy and a potential to create vast employment opportunities. Unfortunately, ‘3D’ industries are shunned by Malaysians particularly among Generation Y (Gen Y) youth. Lack of awareness among Malaysians about ‘3D’ industries is reflected from the high number of foreign workforce engaged in ‘3D’ industries and this is among the reasons for employers to hire them. It is important to know how well Malaysians understand about these industries. Therefore, this paper intends to gauge the level of understanding and perception of Malaysians about ‘3D’ industries through an instrument named ‘3D’ Info System. This survey was conducted among 33 visitors in IIDEX 2019 at Universiti Teknologi MARA (UiTM), Shah Alam. The result shows that 55% of Malaysian visitors have a neutral understanding of ‘3D’ industries, 33% have a poor understanding and only 12% have a good understanding about ‘3D’ industries in Malaysia. Thus, it is recommended that it is vital to create awareness and attract Malaysian job seekers especially Gen Y youth to gain knowledge about ‘3D’ industries in Malaysia.